The role of long noncoding RNAs in cancer: the dark matter matters - Hu, Xiaowen; Sood, Anil K; Dang, Chi V; Zhang, Lin (Current opinion in genetics & development, 2018)
Sequencing technology has facilitated a new era of cancer research, especially in cancer genomics. Using next-generation sequencing, thousands of long noncoding RNAs (lncRNAs) have been identified as abnormally altered in the cancer genome or differentially expressed in tumor tissues. These lncRNAs are associated with imbalanced gene regulation and aberrant biological processes that contribute to malignant transformation. The functions and therapeutic potential of cancer-related lncRNAs have attracted considerable interest in the past few years. Although few lncRNAs have been well-characterized, researchers have recently made impressive progress in understanding lncRNAs and their novel functions, such as regulation of gene expression, metabolism and DNA repair. These latest findings reinforce the crucial roles of lncRNAs in cancer initiation and development, as well as their possible clinical applications.